2013
DOI: 10.1007/s00467-013-2498-4
|View full text |Cite
|
Sign up to set email alerts
|

Serum from minimal change patients in relapse increases CD80 expression in cultured podocytes

Abstract: Background Minimal Change Disease (MCD) is the most common cause of nephrotic syndrome in children and is associated with the expression of CD80 in podocytes with increased excretion of CD80 in urine. We hypothesized that serum from patients with MCD might stimulate CD80 expression in cultured podocytes. Methods Sera and peripheral blood mononuclear cells were collected from subjects with MCD in relapse and remission, and normal controls. Immortalized human podocytes were incubated with culture media contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…CD80 was also detected in the glomeruli of the same patients but were not found in high levels in other NS-causing nephropathies, such as FSGS or membranous nephropathy (MN) 61,62) . These results were confirmed in other populations with MCD 63) , thus leading to the conclusion that high CD80 (B7-1) expression in the urine and glomeruli is a urinary biomarker to distinguish between MCNS and FSGS, which could be used to monitor the activity of the disease 55,66) . Other studies documented the upregulation of glomerular CD80 (B7-1) in patients with diabetic nephropathy 64) and/or with post-transplant FSGS recurrence 65) .…”
Section: Cd80 (B7-1)supporting
confidence: 56%
See 2 more Smart Citations
“…CD80 was also detected in the glomeruli of the same patients but were not found in high levels in other NS-causing nephropathies, such as FSGS or membranous nephropathy (MN) 61,62) . These results were confirmed in other populations with MCD 63) , thus leading to the conclusion that high CD80 (B7-1) expression in the urine and glomeruli is a urinary biomarker to distinguish between MCNS and FSGS, which could be used to monitor the activity of the disease 55,66) . Other studies documented the upregulation of glomerular CD80 (B7-1) in patients with diabetic nephropathy 64) and/or with post-transplant FSGS recurrence 65) .…”
Section: Cd80 (B7-1)supporting
confidence: 56%
“…Other studies documented the upregulation of glomerular CD80 (B7-1) in patients with diabetic nephropathy 64) and/or with post-transplant FSGS recurrence 65) . Sera from MCD patients in relapse, but not in remission, stimulated CD80 expression in cultured podocytes along with diminished nephrin phosphorylation in comparison with podocytes incubated with sera from MCD patients in remission 66) . Therefore, B7-1 may be a biomarker of podocyte injury.…”
Section: Cd80 (B7-1)mentioning
confidence: 88%
See 1 more Smart Citation
“…The exposure of podocytes to LPS rapidly unregulate CD80 in mice and leads to actin reorganization and nephrotic-range proteinuria, whereas mice lacking CD80 are protected from this damage [4]. Sera from MCD patients in relapse, but not in remission, were found to stimulate CD80 expression in cultured podocytes [93]. In addition, urinary concentrations of soluble CD80 in patients with relapsed MCD were significantly higher than those in patients with MCD in remission and with other glomerular diseases including FSGS and in healthy controls [94].…”
Section: Abataceptmentioning
confidence: 99%
“…Then, Garin et al found children with biopsy proven MCD expressed CD80 in their podocytes and excreted high levels of CD80 in their urine during active nephrotic syndrome (33,34). Following these results, they reported sera from MCD patients in relapse stimulates CD80 expression in cultured podocytes (35). In addition, increased CD80 expression in podocyte, glomerular CD80 and urinary excretion of CD80 can be induced by polyIC, a Toll-like receptor 3 ligand, and were associated with proteinuria (36).…”
Section: Idiopathic Nephrotic Syndrome In Asthmamentioning
confidence: 99%